FAMILY ROLE AND MENTAL HEALTH AMONG COMMUNITY-DWELLING OLDER ADULTS: A CORRELATIONAL STUDY IN INDONESIA - Umi Azizah Kusumaningrum; Nasrudin (LPPM STIKES HUSADA JOMBANG, 2026)
Background: Population ageing has become a major public health concern, particularly in low- and middle-income countries where older adults are at increased risk of mental health problems. Family plays a central role in providing emotional, social, and practical support that may contribute to maintaining psychological well-being among older adults. However, evidence regarding the relationship between family role and mental health among community-dwelling older adults in Indonesia remains limited. Objectives: This study aimed to examine the relationship between family role and mental health among community-dwelling older adults in Indonesia. Methods: A community-based correlational study with a cross-sectional design was conducted among older adults residing in Indonesia. Participants were selected using a probability sampling technique and met the predefined inclusion criteria. Data on family role and mental health status were collected using validated structured questionnaires. Descriptive statistics were used to summarize participant characteristics, while the relationship between family role and mental health was analyzed using Spearman's rank correlation test. Statistical significance was determined at p < 0.05. Results: The findings demonstrated that participants who perceived stronger family roles tended to have better mental health status. Statistical analysis revealed a significant positive correlation between family role and mental health among community-dwelling older adults (p < 0.05). Older adults who received adequate emotional support, effective communication, and active family involvement exhibited better psychological well-being and fewer symptoms of emotional distress than those with limited family support. Conclusion: Family role is significantly associated with mental health among community-dwelling older adults. Strengthening family involvement through supportive communication, emotional care, and active participation in daily living may contribute to improved mental well-being in older adults. Family-centered interventions should be incorporated into community health programs to promote healthy ageing and prevent mental health problems among older populations.